A study on supplier selection towards supply chain complexity / Ahmad Faris Abd Aziz, Aleeya Zainol and Ruzaiha Hashim - Abd Aziz, Ahmad Faris; Zainol, Aleeya; Hashim, Ruzaiha (2014)
The supplier selection nowadays becomes complex because there are a lot of criteria need to be clarify in choosing the supplier. The criteria such as geographical location, production, capabilities, price, quality and reputation are gradually gaining equal importance in choosing the supplier. These criteria supposed to easier the company to determine the supplier selection. Hence, this paper aims to find out the relationship of the above criteria towards supply chain complexity. From the findings we recommend that supplier selection should be an open and transparent process, carried out by expert from all key departments and should be done in time to avoid supply chain complexity.